Nematicidal Evaluation of Secondary Metabolites from Bacillus aryabhattai against Reniform Nematode (Rotylenchulus reniformis) using in vitro and in silico Approaches (Indian Journal of Nematology, 2025)
Reniform nematode, Rotylenchulus reniformis is an important nematode associated with castor which causes significant damage to the crop. Search for ecofriendly management options for this nematode resulted in the use of the rhizobacterium, Bacillus aryabhattai as an effective bioagent. In this study, the nematicidal efficacy of crude metabolites of B. aryabhattai was evaluated against the reniform nematode, R. reniformis pre-adult stage in vitro. Nematodes treated with different concentrations of the crude extract of the bacteria were observed at 24, 48, and 72 hrs post-inoculation. The results indicated that a 50% concentration of the crude metabolites was highly effective against the nematodes, with the LC50 of 84.1 mg/ml. The effective metabolite compounds of the bacteria identified through GC-MS analysis viz., 2,4-Di-tert-butylphenol, Docosane, Tetradecanoic acid, Heneicosane, and Tetradecane were docked in silico with the GHF5 (Cellulase) of R. reniformis and based on the binding energy, 2,4-Di-tert-butylphenol was found to be highly effective on the target protein of the nematode. In vitro evaluation of 2,4-Di-tert-butylphenol against R. reniformis revealed that a 5% concentration of the compound exhibited 93.75 per cent mortality of the nematodes. The insights into ligand-target protein interactions described in this study will aid in the rational selection of bacterial biomolecules for the development of commercially viable bionematicidal products.